Keberkesanan perkhidmatan bimbingan dan kaunseling sekolah menengah di Malaysia / Manchelah Natesan - Manchelah , Natesan (2017)
Guidance and Counseling Services in Malaysian secondary schools were introduced in the 1960s during the colonial era. However,the full-time Guidance and Counseling positions were created only in 1996. Guidance and Counseling teachers are exempted from teaching and learning in the classroom. Although the service is being conducted full-time in schools over 20 years, the mass media reports that there is still a high moral collapse among students. This is why there is a need to evaluate the effectiveness of this service to help students understand themselves and their environment positively as in the objectives of the Guidance and Counseling services. This study was conducted based on CIPP Model (Context, Input, Product and Process) by Stufflebeam (1984). A total of 420 counseling teachers in secondary schools from 5 national zones were selected as sample surveys and 5 non-counseling teachers were interviewed to determine the effectiveness of the services in the schools. Interviews with regards to the objectives on the National Philosophy of Philosophy among counseling and non-counseling teachers showed counseling teachers demonstrated high efficiency of the context dimension. The findings also showed that input, process and product dimensions were also high. The results of the Manova Test showed that there was no significant difference in the implementation of Guidance and Counseling services from the input, processes and products dimensions between male and female teachers. Multiple Regression Testing showed that there was a significant influence on the implementation of Guidance and Counseling services from the input dimensions to the Guidance and Counseling services. There was also a significant influence on the implementation of Guidance and Counseling services from the dimensions of the process and products to Guidance and Counseling services in Malaysian secondary schools.